Spectrophotometric Determination of Antidepressant Drug Duloxetine in Pharmaceutical Preparations using π-Acceptors - Sidika Ertürk Toker; Armagan Önal (E-Journal of Chemistry)
In this study, two simple and accurate spectrophotometric methods were presented for the determination of duloxetine hydrochloride (DLX) in pharmaceutical preparations. The methods were based on the reaction of DLX as n-electron donor with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) and 7,7,8,8-tetracyanoquinodimethane (TCNQ) as π-acceptors to give highly colored complex species. The colored products were quantitated spectro-photometrically at 477 and 841 for DDQ, TCNQ, respectively. All variables were studied in order to optimize the reaction conditions. Beer's law was obeyed in the concentration ranges 10.0-50.0 and 15-60 μg mL−1 for DDQ and TCNQ method, respectively. The proposed methods have been successfully applied to the pharmaceutical analysis without any interference from excipients. The suggested procedures could be used for the determination of DLX in pharmaceutical preparations being sensitive, simple and selective.